2004
DOI: 10.1021/cm0401802
|View full text |Cite
|
Sign up to set email alerts
|

Single Source Precursor Approach for the Sol−Gel Synthesis of Nanocrystalline ZnFe2O4 and Zinc−Iron Oxide Composites

Abstract: Nanostructured ZnFe2O4 and zinc oxide−iron oxide composites were obtained by sol−gel processing of a hetero-bimetallic alkoxide. For this purpose the novel molecular precursors Fe2Zn(OR)8 (R = tBu, iPr), fully characterized by spectroscopic and single-crystal diffraction techniques, have been synthesized and their applications in the sol−gel procedure were investigated. The obtained xerogels were annealed at very low temperatures (down to 200 °C) yielding crystalline phases with very small crystallite grain si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(49 citation statements)
references
References 24 publications
1
48
0
Order By: Relevance
“…Most importantly, it is necessary to find an economical and efficient process for the synthesis of ferrite nanocrystals. However, the ferrite nanocrystals are difficult to obtain via using cheap and multiple reactants under moderate conditions [13]. High calcination temperature is always needed to form the MFe 2 O 4 spinel structure, which results in large particles and a broad size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, it is necessary to find an economical and efficient process for the synthesis of ferrite nanocrystals. However, the ferrite nanocrystals are difficult to obtain via using cheap and multiple reactants under moderate conditions [13]. High calcination temperature is always needed to form the MFe 2 O 4 spinel structure, which results in large particles and a broad size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…3. The peaks at 1134.5 and 1163.6 eV corresponded to Eu3d 5/2 and Eu3d 3/2 , respectively [30], which indicated that the Eu ion owns ?3 valence in ZnFe 1.97 Eu 0.03 O 4 nanoparticles [31].…”
Section: Resultsmentioning
confidence: 97%
“…Plocek et al [12] reported the preparation of ZnFe 2 O 4 /SiO 2 nano-composites by the sol-gel method. Veith et al [13] studied the synthesis of nano-crystalline ZnFe 2 O 4 and zinc-iron oxide composites by the sol-gel method. Li et al [14] reported the optical and structural properties of TiO 2 -ZnFe 2 O 4 composite film prepared by r.f.…”
Section: Introductionmentioning
confidence: 99%